2021
DOI: 10.3390/math9202614
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Money on Monetary Policy: Based on DSGE Model Simulations

Abstract: Starting with the interactive relationship between electronic money and household consumption stimuli, this paper deeply analyzes the changes in the behavior of each monetary subject under the impact of electronic money, and establishes a DSGE model based on the three economic sectors of family, commercial bank and central bank under the New Keynesian framework. On this basis, the impact of electronic money on savings, loans, output and the interest rate, and its impact on monetary policy, are described by num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…However, in short-term estimations, inflation has a significant negative effect on the income velocity of money. These results are different from those of previous studies by Al-Tamimi [31], Luo, et al [19], Roy, et al [20], and Khanom [28], which found that the relationship between velocity of money and inflation is positive. Depending on how it affects money balances and income growth more generally, inflation's influence on the velocity of money can be either positive or negative.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in short-term estimations, inflation has a significant negative effect on the income velocity of money. These results are different from those of previous studies by Al-Tamimi [31], Luo, et al [19], Roy, et al [20], and Khanom [28], which found that the relationship between velocity of money and inflation is positive. Depending on how it affects money balances and income growth more generally, inflation's influence on the velocity of money can be either positive or negative.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, electronic money will, to some extent, exacerbate the fluctuations and boost the impact of the money multiplier. Luo, et al [19] analyzed how each type of money changed as a result of electronic money and created a dynamics model based on the family, the commercial bank, and the national bank areas. Their findings indicate that electronic money has unequal effects on deposits and lending while having an unreasonable divergence on households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a research, Luo et al [ 30 ] have tried to find out what effect electronic money has on the monetary policies of different economies and in this way they have used the DSGE model in the New Keynesian framework. The noteworthy point is that in the presented model, three sectors of household, bank and central bank have been analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most studies have primarily used descriptive-analytical methods, while others have examined the issue theoretically. Apart from a few studies such as Zhang and Ma (2011), Owen and Fogelstrom (2005), Luo, Zhou, and Zhou (2021), Ndirangu and Nyamongo (2015), Kitamura (2022), and related studies in Nigeria such as Folarin and Asongu (2019) and Onah, Ujunwa, Ujunwa, and Ogundele (2021), empirical literature has been relatively silent on the implications of electronic money on monetary policy, particularly in developing countries like Nigeria. This knowledge gap is particularly relevant considering the increasing volume of electronic money in Nigeria, the adoption of the e-naira, and the Central Bank of Nigeria's efforts to promote a cashless economy.…”
Section: Introductionmentioning
confidence: 99%
“…This study reviewed a few that have introduced a different approach to the issue. The effect of electronic money on money demand is examined through two main dimensions: the velocity of money and currency circulation (Luo et al, 2021). For instance, Zhang and Ma (2011) utilised multivariate time-series econometric models to analyse the impact of electronic money on money supply using the velocity of money in circulation as an approach in China.…”
Section: Introductionmentioning
confidence: 99%